JOURNALISTIC CULTURE IN THE ONLINE MEDIA OF THE BANDUNG CITY GOVERMANTS PUBLIC RELATIONS - Novrizon Marzal; Mahmoed Mohamed Hosny (Alfuad: Jurnal Sosial Keagamaan, 2022)
The journalistic culture is currently evolving at such a quick pace that it is reflected in the public media held by the Bandung City government. Especially in the online public media, which is administered by the Bandung City government's Public Relations, such as websites, Facebook, Twitter, and Instagram. The goal of this study is to learn more about Bandung City Public Relations' journalistic culture. This study took a qualitative approach and used a qualitative descriptive method, with Kuhlthau's Information Search Behavior Theory, also known as the "Information Search Process" (ISP), as the scalpel. The ISP is divided into six stages: initiation, selection, exploration, formulation, collections, and presentations. Information gathered through interviews with five people who work in the Bandung City Government's Public Relations department. The Research results, First, there are several types of journalistic activities such as news writing, press releases, photography, videography, and media analysis; second, journalistic products such as news, press releases, photos, videos, magazines, and tabloids are produced; third, there is a routine agenda, important indicators, and editorial policies that are implemented; fourth, the existence of a certain point of view in determining the news taken; and fifth, there is a routine agenda, important indicators, and editorial policies that are implemented.